القيادة الخادمة لدى مديري مدارس التعليم الأساسي بمدينة مصراتة وعلاقتها بالثقة التنظيمية (Journal of Academic Research, 2024)
The goal of searching for compatibility between clients of the Directorate of Main Educational Schools in the city of Misurata and trust from their point of view, and therefore the real goals are to search for descriptive interface services, and a questionnaire was prepared consisting of (35) items distributed over the field: The first field: Helping the interface from four distances. The second area: Generalization on nine dimensions. (225) male and female teachers in basic education schools partly affiliated with educational offices were distributed to the facility. They were selected to learn about the importance of randomness. (205) questionnaire sheets were used, and central statistical processing was conducted using the statistical analysis program. (SPSS), where it was The results of the research are as follows: *The degree of basic education school principals’ practice of servant leadership was moderate. * The level of organizational trust was moderate. * There is a strong, statistically significant direct correlation between humility and the dimensions of organizational trust (trust in colleagues and trust in senior management), while the correlation between humility and trust in the manager was weak. *There is a strong, statistically significant, direct correlation between empowerment and the dimensions of organizational trust. *There is a strong, statistically significant positive correlation between caring for teachers first and the dimensions of organizational trust. There is a strong, statistically significant, positive correlation between commitment to developing society and the dimensions of organizational trust (trust in colleagues and trust in senior management), while there is no statistically significant relationship between commitment to developing society and trust in the manager.